Peter Stutchbury : selected projects - Bingham-Hall, Patrick (Sidney : Pesaro publishing, 2010)
"Peter Stutchbury is one of Australia$1 (Bs most awarded and most influential architects. His expressive and environmentally responsible designs point to the new architectural direction of the 21st century, as our built world adapts to the need for sustainability and to a need for reconciliation with the environment. This monograph features Peter Stutchbury$1 (Bs most significant projects, including his delightful harbourside houses in Sydney, the Archery Pavilion for the Sydney Olympic Games, the Birabahn Aboriginal and Torres Strait Islander Centre, and the Deepwater Woolshed. Each of these projects demonstrate Stutchbury$1 (Bs profound knowledge of construction, materials, site and context, as well as his fundamentally intuitive architectural skills. The buildings are presented chronologically, providing a graphic depiction of the architect$1 (Bs evolution. Each project is documented with formal drawings, concept sketches and project descriptions, and illustrated by colour and duotone photographs..."--Publisher description.s
Includes bibliographical references
ARC
Keywords: Stutchbury, Peter -- 1954-; Architect-designed houses -- Australia; Architecture -- Australia -- History -- 20th century; Interior decoration -- Australia